2019
DOI: 10.1111/jns.12320
|View full text |Cite
|
Sign up to set email alerts
|

The utility of Guillain‐Barré syndrome prognostic models in Malaysian patients

Abstract: Guillain‐Barré syndrome (GBS) is an acute immune‐mediated neuropathy that has variable disease course and outcome. The Erasmus GBS outcome score (EGOS), modified EGOS (mEGOS), and Erasmus GBS respiratory insufficiency score (EGRIS) are prognostic models designed to predict the functional outcome of GBS patients at 6 months (EGOS and mEGOS) and the need for mechanical ventilation within a week of admission (EGRIS). The models were primarily developed in the Dutch GBS population, and thus the usefulness of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 27 publications
(53 reference statements)
1
36
1
2
Order By: Relevance
“…The study by Tan et al also provided an AUC value for the group of severely affected (GBS disability score ≥ 3) GBS patients (without MFS), which was similar to the AUC value in our Asian cohort (0.786). 19,20 Model calibration was not described in these studies but could be deduced from the reported results. In both studies, the risk of mechanical ventilation was underestimated by the EGRIS model (Yamagishi et al: predicted probability 13%, observed 17%; Tan et al: predicted probability 23%, observed 44%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Tan et al also provided an AUC value for the group of severely affected (GBS disability score ≥ 3) GBS patients (without MFS), which was similar to the AUC value in our Asian cohort (0.786). 19,20 Model calibration was not described in these studies but could be deduced from the reported results. In both studies, the risk of mechanical ventilation was underestimated by the EGRIS model (Yamagishi et al: predicted probability 13%, observed 17%; Tan et al: predicted probability 23%, observed 44%).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with previous studies that validated the EGRIS in Japan and Malaysia. 19 , 20 Both studies assessed the discriminative ability of the model by comparing EGRIS scores between patients who did and did not require mechanical ventilation within the first week of admission. EGRIS scores were significantly higher for patients who required mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Несмотря на то что mEGOS, как и ее предыдущая версия, в ряде исследований показали высокую достоверность [19,[28][29][30][31], являясь простым, не требующим дополнительных затрат, методом прогнозирования возможности восстановления ходьбы к 6 мес после СГБ на этапе острого периода, данные шкалы несовершенны, что и показали представленные в статье клинические случаи. У обеих пациенток прогноз восстановления в остром периоде, в том числе с использованием шкал EGOS и mEGOS, оказался ошибочным.…”
Section: Introductionunclassified
“…Низкую прогностическую значимость шкал EGOS и mEGOS отметили и другие исследователи [28,35]. Наиболее вероятной причиной подобного несоответствия, на наш взгляд, является отсутствие учета в шкалах нейрофизиологических данных и формы заболевания.…”
Section: Introductionunclassified